Phytoplankton responses to repeated pulse perturbations imposed on a trend of increasing eutrophication. Issue 3 (1st March 2022) - Stelzer, Julio A. A.; Mesman, Jorrit P.; Gsell, Alena S.; de Senerpont Domis, Lisette N.; Visser, Petra M.; Adrian, Rita; Ibelings, Bastiaan W.
Abstract: While eutrophication remains one of the main pressures acting on freshwater ecosystems, the prevalence of anthropogenic and nature‐induced stochastic pulse perturbations is predicted to increase due to climate change. Despite all our knowledge on the effects of eutrophication and stochastic events operating in isolation, we know little about how eutrophication may affect the response and recovery of aquatic ecosystems to pulse perturbations. There are multiple ways in which eutrophication and pulse perturbations may interact to induce potentially synergic changes in the system, for instance, by increasing the amount of nutrients released after a pulse perturbation. Here, we performed a controlled press and pulse perturbation experiment using mesocosms filled with natural lake water to address how eutrophication modulates the phytoplankton response to sequential mortality pulse perturbations; and what is the combined effect of press and pulse perturbations on the resistance and resilience of the phytoplankton community. Our experiment showed that eutrophication increased the absolute scale of the chlorophyll‐ a response to pulse perturbations but did not change the proportion of the response relative to its pre‐event condition (resistance). Moreover, the capacity of the community to recover from pulse perturbations was significantly affected by the cumulative effect of sequential pulse perturbations but not by eutrophication itself. By the end of the experiment, some mesocosms could not recover from pulse perturbations, irrespective of the trophic state induced by the press perturbation. While not resisting or recovering any less from pulse perturbations, phytoplankton communities from eutrophying systems showed chlorophyll‐ a levels much higher than non‐eutrophying ones. This implies that the higher absolute response to stochastic pulse perturbations in a eutrophying system may increase the already significant risks for water quality (e.g., algal blooms in drinking water supplies), even if the relative scale of the response to pulse perturbations between eutrophying and non‐eutrophying systems remains the same. Abstract : Press (eutrophication) and repeated pulse perturbations are antagonistic forces shaping the microbial response to stochastic perturbations. Eutrophication increases the absolute response of the phytoplankton community to pulse perturbations, but does not change the proportionality of response compared to the pre‐event condition. Resistance increase, and recovery decrease after each pulse perturbation independently of the eutrophication process.